Pengalaman Pengobatan Depresi Dengan Nomifensin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1985)
ABSTRACT: The paper describes the epidemiology and pathology of depression. The history of therapy against depression and in particular the neurotransmitters hypothesis is presented. A clinical trial was carried out in the Out-Patient Department of the Central General Hospital Dr. Sardjito, Yogyakarta. Twenty depressed patients with ages of 15 â 25 years were treated with Nomifensine, during two weeks period, with a daily dose of 50 mg in the morning and 50 mg at noon. Intensity of depression was tested with Hamilton Depression Rating Scale, before treatment, a week after treatment and finally two weeks after. A pairwise retest of differences between two item differences, was chosen for analysis of the means of the initial â, mid â, and terminal depression intensity. There is a significant decrease in intensity of depression between the initial and terminal evaluation. Remarkable side effects were absent in almost all the patients treated. Nomifensine in daily dose of 2 X 50 mg a day is effective in the treatment of depression. In most instances reduction in total score can be expected within 1 - 2 weeks of drug treatment. Finally, a recommendation is offered.